CONTRIBUTION A UNE ANALYSE DE LA DYNAMIQUE DE LA VEGETATION DES PARCOURS STEPPIQUES DANS LA REGION DE BISKRA AU SUD-EST ALGERIEN - Kamel-eddine, Bazri; Ghania, Ouahrani (European Scientific Journal, ESJ, 2015)
An ecological analysis is conducted in three sites (EL-Haouche, Zribet El-Oued and Khanguet Sidi Nadji) in a steppes halophytes in the Biskra region (south-east of Algeria). Our analysis shows that the degradation of this steppe and a regressive dynamic of vegetation is very important. The soil is completely stripped and covered with a whitish crust over large areas which results from the rise and deposition of salts on the surface, particularly in Khanguet Sidi Naji. The current situation of these courses is alarming; it requires a serious rational management.